Dynamic spatiotemporal beams that combine two independent and controllable orbital-angular-momenta using multiple optical-frequency-comb lines - Zhe Zhao; Hao Song; Runzhou Zhang; Kai Pang; Cong Liu; Haoqian Song; Ahmed Almaiman; Karapet Manukyan; Huibin Zhou; Brittany Lynn; Robert W. Boyd; Moshe Tur; et al. (Nature Communications, 2020)
Orbital angular momentum takes several forms in structured light beams. Here, the authors demonstrate control of dynamic spatiotemporal beams combining two forms of orbital angular momenta, by coherently adding frequency comb lines.